Interfaith Marriage Post Supreme Court Circular No. 2 of 2023: A Perspective of Hifz al-Din and Constitutional Rights - Elly Lestari; Oyo Sunaryo Mukhlas; Beni Ahmad Saebani (STIT Sirojul Falah Bogor, 2025)
The issuance of Supreme Court Circular (SEMA) No. 2 of 2023 marks a paradigm shift in Indonesian family law, moving from judicial activism that allowed loopholes for interfaith marriages to strict administrative restrictions banning the practice. This study aims to analyze the juridical implications of the Circular by juxtaposing two diametrical perspectives: the doctrine of religious protection (Hifz al-Din) and constitutional rights. This is normative legal research employing statutory and conceptual approaches. The findings indicate that: (1) SEMA No. 2 of 2023 serves as a state manifestation of Sadd al-Dzarai (preventive measure) to maintain theological purity and prevent ambiguity in child lineage status (Hifz anNasl); (2) Within the Indonesian legal system, the right to form a family (Article 28B of the 1945 Constitution) is categorized as a derogable right, restricted by religious values as stipulated in Article 28J paragraph (2); (3) While the Circular establishes legal certainty and judicial uniformity, it potentially triggers legal resistance in the form of law smuggling (fraus legis) through overseas marriages or sham religious conversions. The study concludes that SEMA No. 2 of 2023 reaffirms Indonesia's position as a theistic nation-state that prioritizes theological validity as an absolute prerequisite for the administrative validity of marriage.